The Influence of Interpersonal Communication and Customer Experience on Customer Attitudinal Loyalty: Moderating Role of Switching Costs in B2B Seafood Processing Companies - Bagus Susanto; Masmira Kurniawati (Manunggal Halim Jaya, 2026)
This study examines the effects of interpersonal communication and customer experience on customer attitudinal loyalty, as well as the moderating role of switching costs in the context of business-to-business seafood processing companies. Data were collected through questionnaires distributed to 54 customers of a seafood processing company and analyzed using Structural Equation Modeling to test the relationships among the research variables. The findings indicate that interpersonal communication has a positive and significant effect on customer attitudinal loyalty (β = 0.240; p < 0.05), while customer experience also has a positive and significant effect on customer attitudinal loyalty (β = 0.657; p < 0.01). In addition, switching costs significantly strengthens the relationship between interpersonal communication and customer attitudinal loyalty (β = 0.315; p < 0.05). However, switching costs do not significantly moderate the relationship between customer experience and customer attitudinal loyalty (β = −0.288; p > 0.05). These findings confirm that interpersonal communication and customer experience are important determinants of customer attitudinal loyalty in B2B relationships, whereas switching costs function as a supporting mechanism that strengthens the influence of interpersonal communication but does not strengthen the influence of customer experience. Therefore, B2B seafood processing companies should prioritize strategies aimed at improving the quality of interpersonal communication and delivering superior customer experiences to establish and sustain long-term customer loyalty.